Just Who Loses? : Discrimination in the United States, Volume 2 - Lucas, Samuel Roundfield (Book collections on Project MUSE., 2013)
In Just Who Loses? Samuel Roundfield Lucas continues his penetrating and comprehensive assessment of sex and race discrimination in the United States that he began in Theorizing Discrimination in an Era of Contested Prejudice. This new volume demonstrates that the idea of discrimination being a zero-sum game is a fallacy. If discrimination costs women, men do not necessarily reap the gains. Likewise, if discrimination costs blacks, non-blacks do not reap the gains. Lucas examines the legal adjudication of discrimination, as well as wider public debates about policy on the issue.